Technology Integration in Islamic Education Curriculum Model: A Hermeneutic Study of Mahmud Yunus' Thought - Meiliya Sari, Putri Regina; Abu Bakar, M Yunus (AR-RASYID : Jurnal Pendidikan Agama Islam, 2024)
This study aims to explore the application of Mahmud Yunus' educational concepts in the context of modern Islamic education with a focus on technological integration. Mahmud Yunus emphasized the importance of integration between religious and general sciences as well as active and participatory teaching methods. In this study, Yunus' integrated curriculum approach is explored for application alongside modern technologies such as e-learning and learning apps. The research method uses qualitative analysis of existing educational literature and practices. The results show that technology can enrich the learning experience with dynamic and interactive methods, supporting curriculum integration that balances moral and academic values. However, significant challenges include dependence on technology and privatization of education that can threaten character and social values important in Islamic education. This research suggests the need for strict regulation of technology use, training for educators, and the development of Islamic value-based curriculum guidelines to ensure that technology supports, rather than replaces, the principles of Islamic education. In conclusion, technology should be carefully integrated to improve the quality of education without compromising the essence of Islamic education.